Neonatal Nonketotic Hyperglycinemia: A Severe Case With Prenatal Indicators and Comprehensive Review of Recognition and Management - Samaneh Parviz; Dariush Hooshyar (Clinical Case Reports)
ABSTRACT Nonketotic hyperglycinemia (NKH), also known as glycine encephalopathy, is a rare inherited neurometabolic disorder caused by a deficiency in the glycine cleavage enzyme system (GCS), leading to the pathological accumulation of glycine in blood and cerebrospinal fluid (CSF). This case report details a neonate presenting with central apnea, profound hypotonia, and refractory seizures, alongside prenatal findings of polyhydramnios and hiccup‐like fetal movements, all strongly suggestive of severe NKH. Diagnostic evaluation confirmed markedly elevated glycine levels in serum and CSF, with a CSF‐to‐plasma glycine ratio exceeding 0.08, and ruled out alternative causes of hyperglycinemia. Brain MRI revealed characteristic malformations, corroborating the diagnosis of severe NKH. Treatment included anticonvulsants for seizure management, sodium benzoate for glycine reduction, and NMDA receptor antagonists (ketamine and dextromethorphan) to modulate neurotoxicity. Despite these therapies, the patient demonstrated poor neurodevelopmental outcomes, with rapid progression to severe impairment. This case highlights the significance of early identification, precise diagnosis, and a comprehensive care strategy in managing NKH, aiming to enhance patient outcomes and quality of life.